Efforts to increase enthusiasm for learning through a simple lava lamp-based experiment learning - Sally Geba Latami Telaumbanua (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Education is one of the most essential requirements for national development, as quality education produces quality human beings. The purpose of this study is to create a pleasant learning environment that facilitates students' understanding of the material and encourages active class participation, while also examining the relationship to the Sustainable Development Goals (SDGs). Through research and development (RnD) method in the Thematic KKN service method of the Universitas Pendidikan Indonesia 2022/2023 with the theme "Building Village Existence based on SDG's" and following the 4th SDGs program, namely Quality Education, simple experimental-based learning entitled "Lava Lamp" was held to provide a new color in the learning process in the classroom, especially in science learning. This simple experiment was conducted with all 28 students in Class VII at SMPN Satu Atap Ciawi. The results obtained through this learning experiment showed that students found it easy to focus and understand the material and felt happy during the learning process. In addition, critical thinking skills, creativity, and the ability to solve problems and draw conclusions in students also increased.   Abstrak Pendidikan adalah salah satu syarat penting dalam pembangunan negara, karena dengan pendidikan yang berkualitas akan menciptakan manusia yang berkualitas. Tujuan penelitian ini adalah untuk menciptakan suasana pembelajaran yang menyenangkan sehingga memudahkan peserta didik dalam memahami materi dan melibatkan peserta didik secara aktif di kelas dan menganalisis kaitannya dengan SDGs. Melalui metode research and development (RnD) pada pengabdian KKN Tematik Universitas Pendidikan Indonesia 2022/2023 yang bertemakan "Membangun Eksistensi Desa berbasis SDG's" dan sesuai dengan program SDGs ke-4 yakni Pendidikan yang Berkualitas, pembelajaran berbasis percobaan sederhana berjudul “Lampu Lava” diadakan untuk memberikan warna baru dalam proses pembelajaran di kelas khususnya pada pembelajaran IPA. Percobaan sederhana ini dilakukan pada seluruh kelas VII di SMPN Satu Atap Ciawi yang berjumlah 28 orang. Hasil yang didapat melalui percobaan pembelajaran ini adalah peserta didik menjadi mudah fokus dan memahami materi serta merasa senang selama pembelajaran. Selain itu keterampilan berpikir kritis, kreatif, dan kemampuan dalam memecahkan masalah serta kemampuan dalam menarik kesimpulan pada diri peserta didik juga menjadi meningkat. Kata Kunci: KKN tematik; pembelajaran; percobaan sederhana; SDGs